Konsep Jāhiliyyah dalam Pandangan Sayyid Qutb - Resa, Achmad (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2023)
Jāhiliyyah is commonly understood as a period before the prophecy of Prophet Muhamad. The sending of Prophet Muhammad is the sign that the jāhiliyyah period has ended. Sayyid Qutb, an ulama and writer form Egypt, offered another view of jāhiliyyah. According to him, jāhiliyyah is not mere a period occurred in the past, but it is a condition that occurs now, and will occur in the future. This view consequences the division of the society into Islamic Society and Jāhiliyyah Society. The division of these societies cannot be compromised. The Islamic Society is a society that its law is based on Islamic based law as its law, while the jāhiliyyah society is based on the law that determined by man. Islamic Society and jāhiliyyah society also cannot be gathered in one society. Choosing one of them is denying the other. These two societies will exist along human history. Therefore, jihad is cosmic necessity. The understanding about Islamic Society and jāhiliyyah society is related to Sayyid Qutb’s understanding of Islam. Qutb considers Islam as a liberation to man acknowledment towards the ulūhiyyah of Allah that starts from ‘Aqidah as its base, and syari’at as its implementation of the acknowledgement. Therefore, Islam must change the societal construciton through the law implemented in it. The writer will explain and analyse the concept of jāhiliyyah in view of Sayyid Qutb. The writer uses library research in this research.